KUALITAS PELAYANAN GADRI RESTO YOGYAKARTA (Respon Konsumen sebagai Pendekatan Penelitian) - Setyo Prasiyono Nugroho (Pusat Studi Pariwisata Universitas Gadjah Mada, 2014)
This research is aimed at describing the characteristic model of quality service at Gadri Resto Yogyakarta by asking consumers as this research approach. The research sample is Gadri Resto consumers who are coming to the restaurant for the first time. There are 101 consumers visiting the restaurant. This research employs statistic descriptive method. The variable of this research is measured by tangible, reliability, responsiveness, assurance and emphaty. The data of this research were analyzed by comparing the conclusion based on the consumers’ answer with the result of the interview toward service and management. Besides that, the parameter discussion of knowledge and skill in the assurance variable will be done on the analisis of reliability and responsiveness variables. This is because the knowledge and skill parameters are united meaning that knowledge is the fundamental of skill which is owned by the waiters or waitress. The result of this research shows that the overall of service quality at Gadri Resto has been considered good bt the consumers with the scale 4. In another word, it is also found that consumers felt dissappointed since the service time is taking too long. Whereas, the advantage of basic knowledge parameter (assurance variable) and appearance waiters or waitress (reliability variable) can cover the lackness so the consumers are satified.